Rasio Legis Pengaturan Pekerja Outsourcing dalam Undang-Undang Nomor 13 Tahun 2003 - Fionna Farelita; Made Warka (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the legislative ratio behind the regulation of outsourcing workers in Law Number 13 of 2003, which stipulates that the outsourcing system may only be applied to supporting or auxiliary work as an effort to ensure worker protection and job security. Using a normative legal research method, the study reveals that although the regulation aims to balance corporate efficiency with worker protection, its implementation in practice does not always align with the intention of the lawmakers. The findings indicate that the provisions of Law No. 13 of 2003 have not been optimally implemented, as outsourcing is still applied to core jobs, disparities remain between the protection of outsourced workers and permanent employees, and government oversight remains weak. These deviations and insufficient supervision result in the neglect of outsourced workers’ rights, creating uncertainty in employment relations. Therefore, regulatory harmonization and strengthened supervisory mechanisms are necessary to ensure the legislative ratio of outsourcing regulations is effectively realized in accordance with the principles of fairness in industrial relations